Selection into shift work is influenced by educational attainment and body mass index: a Mendelian randomization study in the UK Biobank. (13th March 2021) - Daghlas, Iyas; Richmond, Rebecca C; Lane, Jacqueline M; Dashti, Hassan S; Ollila, Hanna M; Schernhammer, Eva S; Smith, George Davey; Rutter, Martin K; Saxena, Richa; Vetter, Céline
Abstract: Background: Shift work is associated with increased cardiometabolic disease risk. This observation may be partly explained by cardiometabolic risk factors having a role in the selection of individuals into or out of shift work. We performed Mendelian randomization (MR) analyses in the UK Biobank (UKB) to test this hypothesis. Methods: We used genetic risk scores (GRS) to proxy nine cardiometabolic risk factors and diseases (including educational attainment, body mass index (BMI), smoking, and alcohol consumption), and tested associations of each GRS with self-reported frequency of current shift work among employed UKB participants of European ancestry ( n  =   190 573). We used summary-level MR sensitivity analyses to assess robustness of the identified effects, and we tested whether effects were mediated through sleep timing preference. Results: Genetically instrumented liability to lower educational attainment (odds ratio (OR) per 3.6 fewer years in educational attainment = 2.40, 95% confidence interval (CI) = 2.22–2.59, P  =   4.84 × 10 –20 ) and higher body mass index (OR per 4.7 kg/m 2 higher BMI = 1.30, 95% CI = 1.14–1.47, P  =   5.85 × 10 –5 ) increased odds of reporting participation in frequent shift work. Results were unchanged in sensitivity analyses allowing for different assumptions regarding horizontal pleiotropy. No selection effects were evident for the remaining exposures, nor for any exposures on selection out of shift work. Sleep timing preference did not mediate the effects of BMI and educational attainment on selection into shift work. Conclusions: Liability to lower educational attainment and higher BMI may influence selection into shift work. This phenomenon may bias epidemiological studies of shift work that are performed in the UKB.